2014
DOI: 10.1038/ncomms5401
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial metabolite 2-aminoacetophenone promotes association of pathogenic bacteria with flies

Abstract: Bacteria contaminate insects and secrete metabolites that may affect insect behaviour and potentially fitness through unknown mechanisms. Here we show that the 'grape-like' odorant 2-aminoacetophenone (2AA), secreted by Pseudomonas aeruginosa (a ubiquitous opportunistic human pathogen), facilitates attraction to food for several fly species including Musca domestica, Ceratitis capitata and Drosophila melanogaster. Constant feeding on 2AA increases the level of long-term colonization of the flies' intestine by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…However, many recent studies have reported that odors from bacteria and yeast modulate fly behavior. These odors are detected by D. melanogaster using specialized olfactory receptor proteins Stensmyr et al, 2012;Kapsetaki et al, 2014;Dweck et al, 2015;Falchi et al, 2015). Comparisons of conidia removal in Canton-S flies and orco1 flies indicate that olfactory signals play a significant role in the removal of B. bassiana conidia from the Drosophila body surface.…”
Section: Discussionmentioning
confidence: 99%
“…However, many recent studies have reported that odors from bacteria and yeast modulate fly behavior. These odors are detected by D. melanogaster using specialized olfactory receptor proteins Stensmyr et al, 2012;Kapsetaki et al, 2014;Dweck et al, 2015;Falchi et al, 2015). Comparisons of conidia removal in Canton-S flies and orco1 flies indicate that olfactory signals play a significant role in the removal of B. bassiana conidia from the Drosophila body surface.…”
Section: Discussionmentioning
confidence: 99%
“…Here, based on the functional roles of some of these genes, we present hypotheses on how D. nigrosparsa might have adapted. Or49b and Or42a are known to play an important role in the attraction to aromatic and alcoholic compounds related to food1448, while Or56a is pivotal in the detection of geosmin, a volatile toxic compound produced by a number of fungi49, bacteria50, and cyanobacteria51, which activates a conserved pathway among all Drosophila species, triggering a single class of sensory neurons and targeting the DA2 glomerulus (Fig. 8)40.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa strain UCCBP 14 (PA14) and isogenic gene deletion mutants Δmvfr, ΔphzS, ΔphzS and ΔrhlR/ΔlasR are previously described (Rahme et al 1995;Kapsetaki et al 2014). E. coli MGH and E. coli BWH and all other strains used (but Lactobacillus ones) are human isolates obtained from Prof. Elizabeth Hohmann at Mass General Hospital and Prof. Andrew Onderdonk at Brigham and Women's Hospital.…”
Section: Bacterial Stainsmentioning
confidence: 99%
“…Adult Oregon R 3-5 day old flies were infected for 24 hours with a mix of bacterial culture(s) grown as mentioned above, pelleted and diluted to a final OD 600nm 0.02 per strain in a 4% sugar (sucrose or glucose) medium. Flies were then transferred and maintained in modified falcon tubes with 200μl 2% or 4% of sucrose or glucose as previously described (Kapsetaki et al 2014). At day 2 and day 5 flies were homogenised using the Qiagen Tissuelyser LT for 5 minutes at 50Hz.…”
Section: Fly Colonisationmentioning
confidence: 99%